Anesthetic approach to adult moyamoya disease: A case report Erişkin moyamoya hastasına anestetik yaklaşım: Olgu sunumu - Said Aydoǧan, M.; YÜCEL, AYTAÇ; ÖZGÜL, ÜLKÜ; Öztürk, Erdoǧan; Konur, Hüseyin; Namik Öztanir, MUSTAFA NAMIK; ÖZTANIR, MUSTAFA NAMIK; Özcan Ersoy, M. (My University, 2010)
Moyamoya disease is an entity, which is caused by obstruction or stenosis in the area between the internal carotid artery, and anterior and middle cerebral arteries, identified angiographically, and does not have an exactly known etiology. The most frequent symptoms of onset are hemorrhage in adults and ischemia in children. In the treatment of moyamoya disease revascularization surgery is performed in order to decrease the vascular fragility. A specialized care is required in the perioperative period since surgery is often complicated by cerebral ischemia or cerebral hemorrhage. Aim in the perioperative anesthetic management is to provide the balance between oxygen supply to and use in the brain. In this case report we aimed to discuss the anesthetic management in a 22-year-old male patient with moyamoya disease in whom a multipl burr hole surgery was performed. © Gülhane Askeri Ti{dotless}p Akademisi 2010.